History and Problems of Political Conflict in the Integration of Turkish-Speaking States (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The article describes the history of the Organization of Turkic states, the political and economic factors that led to the delay in integration, and the role of historical processes in the integration of Turkic states. The conflicts between the Turkic states and the prospects to end the conflicts, the current problems of economic and political cooperation, the threats against the Turkic integration and the influence of geopolitical processes on integration are analyzed.